Studies on Breeding and Feeding Practices of Buffalo in Vogue among Buffalo Farmers in Temperate Himalayan Region of Kashmir Valley - Dar, Parwaiz Ahmad; Khan, Azmat Alam; Shah, Anees Ahmad; Qadri, Ishfaq Ahmad; Manzoor, Ashiq; Khan, Hilal Musadiq (Indian Journal of Hill Farming, 2018)
The study was conducted in two geographically isolated districts of Anantnag in south Kashmir and Baramulla in north Kashmir. In each district 200 buffalo rearing farmers were selected. The information was collected through personal visit on the basis of a pre-formulated and tested questionnaire. The results revealed that majority (81.50%) of respondents were detecting heat in buffaloes by themselves and natural service with known/unknown bull was the only method of mating. Only a meagre proportion (8.75%) were practicing pregnancy diagnosis and considerable number of farmers (48.00%) were using services of a veterinarian for the treatment of anoestrous. Grazing plus supplementary feeding was adopted by maximum proportion of respondents (95.50%) with 58.25% using a combination of green fodder and dry fodder. Feeding twice a day was adopted by maximum (76.50%) farmers and feeding regularity was maintained by majority (89.75%). Treatment of poor quality feed stuffs was not practised by any of the farmers. Majority of the respondents (97.75%) were not feed according to animal’s productivity level while 76.50% were practicing feeding at later stage of dry period. All farmers practiced feeding as per body weight and all of them used milk as a source feeding to young stock. Proportion of farmers, feeding according to productivity level and those feeding at later stage of dry period differed significantly among the districts. Majority (92.50%) of the respondents adopted individual pattern of feeding. It is concluded that many of the breeding and feeding practices in vogue did not conform to any prescribed standards and as such farmers need to be apprised about scientific management practices.